2009
DOI: 10.1590/s0102-76382009000200012
|View full text |Cite
|
Sign up to set email alerts
|

Comparação entre exercícios de respiração profunda e espirometria de incentivo no pós-operatório de cirurgia de revascularização do miocárdio

Abstract: Objective: To compare the effects of deep breathing exercises (DBE) and the flow-oriented incentive spirometry (IS) in patients undergone coronary artery bypass grafting (CABG) through the following variables: forced vital capacity -FVC, forced expiratory volume in 1 second -FEV 1 , maximal respiratory pressures and oxygen saturation.Methods: Thirty six patients in CABG postoperative period underwent thirty minutes of non-invasive ventilation during the first 24 hours after extubation and were randomly shared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 24 publications
3
26
0
6
Order By: Relevance
“…In addition, training of the respiratory muscles provides greater capacity to physical exercise and greater tolerance to fatigue. 33 Renault et al (2009) 34 have compared the effects of Exercises of Diaphragmatic Breathing (EDB) and Incentive Spirometer (IS) in patients undergoing coronary artery bypass grafting surgery by using the following variables: forced vital capacity; first-second forced expiratory volume, maximal respiratory pressures, and oxygen saturation. Those authors have reported no significant differences in the respiratory variables studied in patients undergoing EDB and IS in the post-operative period of coronary artery bypass grafting surgery.…”
Section: Physical Exercises During Hdmentioning
confidence: 99%
“…In addition, training of the respiratory muscles provides greater capacity to physical exercise and greater tolerance to fatigue. 33 Renault et al (2009) 34 have compared the effects of Exercises of Diaphragmatic Breathing (EDB) and Incentive Spirometer (IS) in patients undergoing coronary artery bypass grafting surgery by using the following variables: forced vital capacity; first-second forced expiratory volume, maximal respiratory pressures, and oxygen saturation. Those authors have reported no significant differences in the respiratory variables studied in patients undergoing EDB and IS in the post-operative period of coronary artery bypass grafting surgery.…”
Section: Physical Exercises During Hdmentioning
confidence: 99%
“…The technique involves the application of CPAP with pressure levels ranging from 30 to 45 cmH2O pulmonary complications after cardiac surgery [5,6]. When approaching these cases, respiratory physiotherapy has been increasingly requested, since it uses techniques that can improve respiratory mechanics, reexpansion pulmonary and bronchial hygiene.…”
Section: Alveolar Recruitment Techniquesmentioning
confidence: 99%
“…Among these, we can highlight the Respiron® IS, which emphasizes the deep inspiration up to total lung capacity, providing visual feedback 7,8 . This type of IS facilitates deep breathing, stimulates high inspired volumes and prevents lung hypoventilation 6,9,10 .…”
Section: Introductionmentioning
confidence: 99%